FORMULATION AND EVALUATION OF FUNCTIONAL BEVERAGES INSTANT POWDER COMBINATION OF THE BUAS-BUAS LEAVES (Premna serratifolia L.), SECANG WOOD (Caesalpina sappan L.) AND GINGER Rhizome (Zingiber officinale R.) - Putri, Dinda Marlinda; Isnindar, Isnindar; Luliana, Sri (Universitas Tanjungpura, 2023)
BACKGROUND: The use of buas-buas leaves (Premna serratifolia L.), sappanwood (Caesalpina sappan L.) and ginger rhizomes (Zingiber officinale R.) as raw materials for instant powder drink is to make it easier to serve and has health benefits. OBJECTIVE: This study aims to determine the physical characteristics and the level of public preference for instant powder drinks. METHOD: This research is an experimental study with sugar crystallization as a method of making instant powder made in 4 different formulas. Data collection was carried out to respondents through questionnaires with a total of 20 respondents. Data analysis was performed using Oneway ANOVA on the SPSS program. RESULTS: The results showed that the resulting powder had a yellow to orange color with a distinctive aroma of wild leaves, the powder had a smooth and dry texture. CONCLUSION: The four formulas met the physical properties requirements of instant powder and F2 became the most preferred formula.Keywords: buas-buas leaves, sappan, ginger, instant powder